Investigating the Mechanical, Physical and Biological Properties of PMMA/TiO2 Composites with Nanoclay for Denture Applications - AHMED, Shaymaa J.; ABDULRIDHA, Nazar J.; AL-OBAIDI, Anwer J.; DALFI, Hussein; ALOMARAH, Amer (Engineering Transactions, 2025)
Prosthodontics uses permanent or removable dentures to replace missing teeth, with partial dentures made from cobalt chromium and full dentures from acrylic resin. This study presents Veracril self-curing acrylic, a material for hybrid artificial denture composites reinforced with montmorillonite (MMT) and titanium oxide (TiO2) particles. It is softer, lighter, and more stable than previous materials. Several experiments (mechanical, physical, and biological) have been carried out to examine the novel composite at various MMT and TiO2 weight ratios. The findings indicate that these additives significantly improve the mechanical properties of the matrix material, making it suitable for denture manufacturing. The addition of MMT as a filler enhances bonding between the matrix and additives. The additives’ success in biological tests, including antibacterial activity and toxicity assessments, further supports their suitability for dental applications.